2019
DOI: 10.1038/s41598-019-52228-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective-precipitations process on the corrosion resistance and hardness of dual-phase high-carbon steel

Abstract: It is commonly known that precipitation of secondary phase in non-ferrous alloys will affect the mechanical properties of them. But due to the nature of dual-phase low-alloy high-carbon steel and its high potential of precipitation of cementite, there is limited study on tailoring the mechanical and corrosion properties of this grade of steel by controlling the precipitation of different phases. Predicting and controlling precipitation behaviour on this grade of steel is of great importance towards producing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Results showed that due to multi phases, hardness and corrosion performance improved, as fractions of bainite constituents increased at a low of martensite fractions. Similar studies [15,16] on high carbon low alloyed steel had also been executed at different austenitiza-tion temperatures with controlled soaking time and quench rates. Results have shown that hardness increases by using lower austenitization temperature at the expense of corrosion resistance.…”
Section: Strength and Plasticitymentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that due to multi phases, hardness and corrosion performance improved, as fractions of bainite constituents increased at a low of martensite fractions. Similar studies [15,16] on high carbon low alloyed steel had also been executed at different austenitiza-tion temperatures with controlled soaking time and quench rates. Results have shown that hardness increases by using lower austenitization temperature at the expense of corrosion resistance.…”
Section: Strength and Plasticitymentioning
confidence: 99%
“…Samples at 10 kW induction power have shown high corrosion resistance due to the presence of soft phases (i.e. pearlite), which keep decreasing as heating time increases with the formation of martensitic structure (since pearlite behaves as cathodic regions, while martensite becomes anodic [15]). Multiphase microstructure in steel always causes galvanic corrosion due to the presence of microcells.…”
Section: Electrochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The wire rod rolled by structural steel with carbon content not less than 0.6% is called high-carbon hard-wire steel, which is widely used in construction, transportation, and other industries [1][2][3]. Nonmetallic inclusions affect the mechanical properties and corrosion performance of steel [4]. Compared with low-carbon steel, high-carbon steel has high hardness and low ductility and is more sensitive to nonmetallic inclusions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…High-carbon hard wire steels are mainly applied in massive engineering projects such as bridges, cables, airports, power stations, and dams [ 1 , 2 , 3 ]. High-carbon hard wire products are drawn into filaments with a diameter of about 5 mm [ 4 , 5 ]. The hard inclusions with large sizes affect the steel yield and performance.…”
Section: Introductionmentioning
confidence: 99%